The Moderating Role of Profitability and Firm Size in ESG Disclosure Towards Firm Value - Rahmah, Nafilah Alfa; Purwohedi, Unggul; Handarini, Dwi (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
In this article, we examine the impact of ESG disclosure on firm value, with profitability and firm size serving as moderating variables. It utilizes balanced panel data from companies consistently listed in the IDX ESG Leaders index at any point in the observation period from January 2023 to March 2024. The data is derived from ESG score announcements by the Indonesia Stock Exchange and company financial reports. Moderated regression analysis is conducted using EViews software. The study employs two proxies for the dependent variable as a robustness test. The findings demonstrate that ESG disclosure has a negative and significant effect on firm value, as measured by Tobin's Q and Price-to-Book Value (PBV). Moreover, profitability and firm size moderate this relationship by reducing its negative impact. The implications of these results show that ESG disclosure is not always received positively by the market, where this has an impact on reducing firm value. Nonetheless, this impact can be minimized by profitability and firm size, which serve as additional signals for increasing market acceptance of ESG disclosures. Further research is recommended to expand the sample and observation period, add other variables that influence firm value, analyze without data transformation, or focus research on certain sectors.